Cell Counts, rather than Proportion, of CD8/PD-1 Tumor-Infiltrating Lymphocytes in a Tumor Microenvironment Associated with Pathological Characteristics of Chinese Invasive Ductal Breast Cancer - Qingkun Song; Feng Shi; Maya Adair; Hong Chang; Xiudong Guan; Yanjie Zhao; Yuchen Li; Guangjiang Wu; Jiangping Wu (Journal of Immunology Research)
Objective. This study is aimed at investigating the association of exhausted CD8+ tumor-infiltrating lymphocytes with clinic-pathological factors. Methods. 133 patients diagnosed with primary invasive ductal breast cancer were recruited into the cross-sectional study consecutively. Immunohistochemistry was used to detect biomarker expression on formalin-fixed and paraffin-embedded sections. Double staining of CD8 and PD-1 was conducted on lymphocytes. Results. The proportion of CD8+/PD-1- TILs was 16% among patients with axillary lymph node metastasis, significantly lower than those without metastasis (24%). The expression of CK7, CK20, or Ki-67 was not related with the proportion of phenotypes of CD8/PD-1 TILs. Younger patients had more cell counts of CD8+/PD-1- TILs than elderly patients (18/HPF vs. 9/HPF, p<0.05). Patients with axillary lymph node metastasis had less CD8+/PD-1- TILs than those without metastasis (11/HPF vs. 27/HPF, p<0.05). Median counts of CD8+/PD-1- TILs among patients with CK20 and E-Cad expression were 33/HPF and 14/HPF, significantly higher than those among patients with negative CK20 (16/HPF) and E-Cad expression (6/HPF). Ki-67 index had a significant correlation with cell counts of CD8+/PD-1+ TILs and CD8+/PD-1- TILs, and the correlation coefficients were 0.19 and 0.21 (p<0.05), respectively. Conclusion. The proportion of CD8+/PD-1- TILs was related with metastatic status of the axillary lymph node but cell counts of CD8+/PD-1- TILs were related with metastatic status of the axillary lymph node and expression of CK7, CK20, E-Cad, and Ki-67. Absolute cell counts, not proportion of CD8/PD-1 TILs, were more likely to distinguish clinic and pathologic characteristics of breast cancer.